Trustworthiness Requirements in Information Systems Design: Lessons Learned from the Blockchain Community - Irina Rychkova; Marwa Ghriba (Complex Systems Informatics and Modeling Quarterly)
In modern society, where digital security is a major preoccupation, the perception of trust is undergoing fundamental transformations. Blockchain community created a substantial body of knowledge on design and development of trustworthy information systems and digital trust. Yet, little research is focused on broader scope and other forms of trust. In this study, we review the research literature reporting on design and development of blockchain solutions and focus on trustworthiness requirements that drive these solutions. Our findings show that digital trust is not the only form of trust that the organizations seek to reenforce: trust in technology and social trust remain powerful drivers in decision making. We analyze 56 primary studies, extract and formulate a set of 21 trustworthiness requirements. While originated from blockchain literature, the formulated requirements are technology-neutral: they aim at supporting business and technology experts in translating their trust issues into specific design decisions and in rationalizing their technological choices. To bridge the gap between social and technological domains, we associate the trustworthiness requirements with three trustworthiness factors defined in the social science: ability, benevolence and integrity.